AC conductivity and dielectric properties of Cr2O3 doped SrO–P2O5 glasses - El-Damrawi, G.; Abdelghany, A.M.; Madshal, M.A. (Physica. B, Condensed matter, 2021)
Cr2O3 doped glasses in the binary SrO–P2O5 system were synthesized via melt annealing route. The dielectric behaviors of studied glasses were collected using automated broadband dielectric spectroscopy within the frequency interval (0.1 Hz–20 MHz) in a temperature range between 323 and 473 K. The dielectric spectroscopy is applied to shed light on both the dielectric constant and the electrical modulus of the investigated glasses. The ac conductivity changes with changing of both frequency and temperature with minor changes attributed to the change in chromium oxide concentration. Both the dielectric constant and dissipation loss is decreased with increasing frequency. On the other hand, they increased with increasing temperature in the low-frequency region for all the prepared samples. Correlated barrier hopping (CBH) is considered an appropriate conduction mechanism results from the decrease of frequency exponent (s) with the increase in temperature. •SrO-P2O5 glasses doped with minor amount of Cr2O3 were prepared.•Prepared samples were studied using automated broadband dielectric spectroscopy.•Both the dielectric constant and dissipation loss are decreased with increasing frequency.•Correlated barrier hopping (CBH) is considered as an appropriate conduction mechanism.